2021
DOI: 10.1007/s11604-021-01143-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature alteration on viscosity, polymerization, and in-vivo arterial distribution of N-butyl cyanoacrylate-iodized oil mixtures

Abstract: Purpose Temperature alteration can modify the polymerization of n-butyl cyanoacrylate (NBCA)-iodized oil mixtures during vascular embolization; its effects on viscosity, polymerization time, and intra-arterial distribution of the NBCA-iodized oil mixture were investigated. Materials and methods In vitro, the viscosities of NBCA, iodized oil, and NBCA-iodized oil mixtures (ratio, 1:1–8) were measured at 4–60 ºC using a rotational rheometer. The polymerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…27 It has been shown that with a reduction in temperature, cyanoacrylate viscosity increases, and this may also alter polymerisation rates. 28 To standardise our measurements across all samples and for the duration of the testing period, the samples were therefore incubated at 37°C. This was done to ensure that the samples were not exposed to the ambient temperature of the lab, but rather 37°C consistent with the expected temperatures in vivo and that all samples were subjected to the same corresponding increase in temperature that would be expected to occur in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…27 It has been shown that with a reduction in temperature, cyanoacrylate viscosity increases, and this may also alter polymerisation rates. 28 To standardise our measurements across all samples and for the duration of the testing period, the samples were therefore incubated at 37°C. This was done to ensure that the samples were not exposed to the ambient temperature of the lab, but rather 37°C consistent with the expected temperatures in vivo and that all samples were subjected to the same corresponding increase in temperature that would be expected to occur in vivo.…”
Section: Discussionmentioning
confidence: 99%